Grit relates to academic performance among college students: a five year systematic literature review - Sulong, Rose Manisah; Ahmad, Nor Aniza; Yanling, Liu; Ruihua, Li (South East Asian Association for Institutional Research, 2024)
In recent years, many scholars have studied the influence of non-cognitive factors on academic success, including grit. However, few studies comprehensively analyze the connection between grit and academic outcomes with university learners. Therefore, the research aims to explore how grit affects their academic performance in the context of higher education. This paper presents a comprehensive, systematic review of 13 studies between 2018 and 2023 from two databases: Scopus and Web of Science. The selection criteria focus on empirical research, including the impact of grit on academic achievement. This review finds that grit has a great influence on academic success. It is worth mentioning that perseverance of effort (POE) and consistency of interest (COI), which are two aspects of grit, seem to have different effects on academic performance. In addition, further study on the correlation of grit and other factors with college learners' academic performance can be considered to provide alternative and new ideas for improving students' academic performance.